Os NPCS de vampyr : a simulação social em jogos digitais narrativos - Rypl, Victor Ramires (2022)
This research aims to understand how social simulation systems are utilized in single player narrative digital games, through the functioning of the non-player characters (NPCs), supported by an analysis of the game Vampyr (Dontnod Entertainment, Focus Home Interactive, 2018). This work is aided by a bibliography review on the development of non-player characters (NPCs), their social skills and different social representations within games.The chosen methodology for this analysis was the building blocks method suggested by Clara Fernandez-Cara, developed specifically for games, which allows one to understand how different elements of the language relate to one another. The results show the fundamental role NPCs play in deepening the narrative and the creation of the game’s world. The structure social simulation provides also enhances the game’s capacity of expanding the themes selected by the developers, showing the potential this mechanic and games as a whole have in contributing to the communications field.